Combined disease modifying treatment of rheumatoid arthritis with methotrexate and hydroxychloroquine - N A Sergiets; N K Erov (Научно-практическая ревматология)
Objective. To compare efficacy of different variants of combined disease modifying treat- ment in rheumatoid arthritis (RA). Material and methods. 46 pts with RA (group 1a) received methotrexate 7,5 mg/week, hydroxychloroquine 200 mg/day, diclofenac 100 mg/day. 36 pts (group 1b) were treated with the same doses of methotrexate and hydroxychloroqune combined with low doses of glucocorticoids (GC). 60 pts with RA were included in group of comparison. 36 from them (group 2a) received methotrexate and diclofenac, 24 (group 2b) – methotrexate, diclofenac and low doses of GC. Folic acid 1-2 mg/day 5 days a week was prescribed to all pts. Efficacy assessment was performed after 6 and 12 months of treatment. Joint inflammation score was used as outcome measure. Results. In group 1a after 6 months good response was achieved in 21,4%, moderate response – in 67,8% and no response – in 10,7%, in group 1b – in 33,3%, 63,3% and3,3%, in group 2a – in 8,3%, 70,8% and 20,8% respectively. In group 2b good response was achieved in 38,3% and moderate – in 61,1%. In group 1 pts significant improvement was achieved earlier and more frequently (p<0,01). After 12 months in group 1b pts good response was more frequent than in group 1a and 2b pts. Adverse events appeared mainly during the first 6 months of treatment in pts not receiving folic acid. Conclusion. In pts receiving combined disease modifying treatment of RA with methotrex- ate and hydroxychloroquine good response was more frequent and no response was less frequent than in those receiving monotherapy with methotrexate.